Assessing total factor productivity across Africa: an empirical investigation - (:unkn) unknown (My University, 2022)
Even though Africa is home to many emerging markets, the attention on African growth might be neglected by economists and scholars due to data unavailability and this segment’s minor impact on the world economy. In this paper, we investigate the evolution of total factor productivity (TFP) growth in selected African countries during 1980–2017. By applying an economic approach, a robust nonparametric approach is used to address heterogeneities in production technologies among African countries. Based on a dynamic conditional reference set with the scenario analysis, the proposed model allows us to improve the approximate production frontier by selecting homogeneous references in terms of economic structures. Furthermore, an additive TFP indicator is applied to identify productivity gains among regions and countries operating in Africa. The results show that the range of annual productivity growth rate in Africa is between 0.73 and 4.29% when convex technology and aggregate directional distance function is applied. The finding also indicates Africa growth is mostly driven by scale efficiency improvement and technological progress.
Keywords: African Research